A CRITICAL LOOK AT EVOLUTION OF PRINTING PRESS AND CONSTRUCTION OF PUBLIC CONSCIOUSNESS - Behera, Hrushikesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focuses on the process of print and how it influences people’s and society’s habits and practices. This research is going to talk about some of the technological and historical occurrences that have occurred in the evolution of print media in India. In this way, Western European concerns over printing technology are linked to and related to a global context. Later, the research looked into the difficulties and complications that arose throughout the development of Odisha’s print media in the late 19th century and 20th century.